2016
DOI: 10.1038/ncomms13288
|View full text |Cite
|
Sign up to set email alerts
|

Carbene footprinting accurately maps binding sites in protein–ligand and protein–protein interactions

Abstract: Specific interactions between proteins and their binding partners are fundamental to life processes. The ability to detect protein complexes, and map their sites of binding, is crucial to understanding basic biology at the molecular level. Methods that employ sensitive analytical techniques such as mass spectrometry have the potential to provide valuable insights with very little material and on short time scales. Here we present a differential protein footprinting technique employing an efficient photo-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
103
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(113 citation statements)
references
References 40 publications
(50 reference statements)
5
103
0
2
Order By: Relevance
“…As we noted previously and confirmed recently by Oldham et al [29], freezing increases the yield of insertion. We observed this to be true for all three reagents.…”
Section: Restricting Diffusionsupporting
confidence: 75%
See 1 more Smart Citation
“…As we noted previously and confirmed recently by Oldham et al [29], freezing increases the yield of insertion. We observed this to be true for all three reagents.…”
Section: Restricting Diffusionsupporting
confidence: 75%
“…More recently, diazirine precursors have been incorporated into cross-linkers [27,28] and covalent labeling agents [23,29,30]. BCarbene footprinting^has been successfully demonstrated using gaseous diazirine [30], simple aliphatic diazirines [23,31,32], and most recently aromatic diazirine derivatives [29]. Carbene labeling appears to offer the hallmarks of an excellent, adaptable labeling tool.…”
mentioning
confidence: 99%
“…Reactive-species footprinting (prototype is •OH) provides general and fast reactions. [8] Fast photochemical oxidation of proteins (FPOP) (Fig.S1, SI p 3) affords a ready opportunity for broad-based implementation especially if the number of reactive species can be expanded to give broad coverage. [9] …”
mentioning
confidence: 99%
“…Such methods have enabled MP folding to be monitored [215]. These fast reacting functional groups have recently been extended further to include diazirines which are also activated by laser irradiation [230,231]. This approach has the advantage that the diazirine probes used are membrane permeable, as shown by a recent study in which the majority of modifications were shown to be located in the transmembrane region of the MP, OmpF [231].…”
Section: Discussionmentioning
confidence: 95%
“…Recent work has revealed that a small hydrophobic, trifluoromethyl aryldiazirine probe could be used to footprint the membrane spanning regions of trimeric E. coli OmpF, with the trimerisation interface remaining relatively unlabeled when compared with the remainder of OMP [230,231]. A complementary approach to label proteins with trifluoromethyl radicals ( Å CF 3 ) has also been described recently [232].…”
Section: Other Chemical Labelling Methodsmentioning
confidence: 99%